PENGARUH MEDIA PENDINGIN DAN WAKTU TUNGGU TERHADAP POROSITAS, KEKERASAN DAN STRUKTUR MIKRO MATERIAL AL PADUAN (RONGSOKAN) MENGGUNAKAN METODE PENGECORAN EVAPORATIVE - Komang Aria Kresna Kepakisan; Rudi Siswanto (Universitas Lambung Mangkurat, 2019)
The purpose of this research is to know the effect of cooling media and holding time to porosity, hardness and micro structure of Al alloy material (scrap) using evaporative casting method. The method used in this research is the experimental method of smelting Al Alloy piston scrap and poured at 700°C in Styrofoam pattern mold with 10 and 15 minutes holding time, then cooled with medium air, brine, and water of PDAM for 30 minutes. The material used is excavator aluminum alloy (scrap) izumi piston with silicon aluminum alloy (Al-12% Si). The highest hardness value obtained from the results of cooling casting with the brine cooling medium for 10 minutes that is equal to 217,996 kg / mm2 average HV. At porosity, the highest value was obtained at holding time of 15 minutes with PDAM water cooling medium 5.088% against raw material. While the result of visual observation with 50x magnification of microstructure of specimen to raw material, Si material in raw material has significant length increase. The conclusion of the research results is that re-casting with variations of cooling medium and waiting time will increase hardness and increase porosity, except on brine cooling medium. Keywords: MTTR, MTTF, RCM (Reliability Centered Maintanance)